Makna Idiomatik Pada Nama-Nama Rumah Makan di Kota Padang - Fira Rahmadaniaulia; Afrini Rahmi; Yulia Pebriani (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This research is motivated by the names of restaurants in Padang City which have idiomatic meanings, both full idioms and partial idioms. This research is also based on the reason for the naming of restaurants in Padang City which has its own reasons from the owner of the restaurant so that it can be created and inspired in using that name as the name of the restaurant. The type of research used in this research is qualitative research with descriptive method. The data in this study is the text of the nameplate of restaurants in the city of Padang based on full idioms and partial idioms. The research data was collected using several techniques, namely observation techniques, interview techniques, documentation techniques and field notes techniques. The data were analyzed using a spradley model consisting of input, process and output. Based on the results of the study it was found that: Based on the results of the research in chapter IV it can be concluded that: the naming of the restaurant has a full idiom meaning as much as 20 data. The meaning of the partial idiom was found as many as 33 data. The reason for naming restaurants in Padang City is based on the inventor and maker, namely 19 data, because of the naming based on the material there are 6 data and the reason for naming that is also found is the mention of the nature there are 28 data.